The Influence of the Teacher's Role in Increasing the Learning Independence of Mobile-assisted Elementary School Students - Ova Huzaefah; Yuanyuan Wang; Zhang Wei; Dhini Mufti; Friscilla Wulan Tersta (Yayasan Adra Karima Hubbi, 2024)
Background. The role of the teacher to increase student learning independence will be very influential. Teachers will be able to help students to carry out learning activities independently. So this will provide opportunities for students to be active during learning. The teacher will be a motivator to increase students' interest, enthusiasm, and self-confidence. This will provide a new enthusiasm for students to do things independently. Independence will also help students be more responsible in doing things. Purpose This study aims to determine how much the teacher's role is in increasing learning independence for students. Teachers who are a place of aspiration for students at school will play an important role in the development of students in the world of education. In addition, it also aims to provide an overview of the development of strategies and methods to support the needs in the process of independence for students. Method. The method used in this research is a quantitative method. This method is a form of data collection in the form of numbers that can be tested. The data obtained is the result of the acquisition of responses from the distribution of questionnaires containing questions regarding the influence of the teacher's role in increasing student learning independence. The statement in the form of a questionnaire is presented in the form of google from which is shared via whatsapp. The collected data will be accessed into excel to be processed using SPSS. Results. The results of this study state that teachers as parents in formal schools have a big role in the efforts of learning independence for students. Providing opportunities for students to be active in learning will provide opportunities towards learning independence. Appreciation and motivation from teachers will increase students' interest in learning. This will help students in overcoming learning difficulties. Teachers can provide guidance to improve students' learning independence. Conclusion This research can be concluded that students need the role of the teacher as a support for increasing independence in learning. Students' independence in learning will affect their daily lives. In addition, it will help students to increase self-confidence, responsibility, initiative, and self-control. So that students are expected to be able to plan the learning process, seek information, and also evaluate learning outcomes.